Symposium introduction: Minding the modern: Human agency, intellectual traditions, and responsible knowledge by Thomas Pfau - TSE, Justin Kh (Institutional Knowledge at Singapore Management University, 2015)
Pfau opens with the point that the concepts in the book aren’t tools to be used. For Pfau, a concept is like a person. You can’t use concepts; you have to engage them. You have to know their histories, the way they passed on their traditions and their stories, because concepts are a remembrance of the past. They also grow—or, as John Henry Newman put it—they develop. You have to let a concept breathe, talk, walk. To use a concept—indeed, to be complicit in the modern academic culture’s practices of applying theories and skimming books—is what (for Pfau) is paralyzing the humanities.